Who is reporting non‐native species and how? A cross‐expert assessment of practices and drivers of non‐native biodiversity reporting in species regional listing - Castro, Andry (2023)
Each year, hundreds of scientific works with species' geographical data are published. However, these data can be challenging to identify, collect, and integrate into analytical workflows due to differences in reporting structures, storage formats, and the omission or inconsistency of relevant information and terminology. These difficulties tend to be aggravated for non-native species, given varying attitudes toward non-native species reporting and the existence of an additional layer of invasion-related terminology. Thus, our objective is to identify the current practices and drivers of the geographical reporting of non-native species in the scientific literature. We conducted an online survey targeting authors of species regional checklists—a widely published source of biogeographical data—where we asked about reporting habits and perceptions regarding non-native taxa. The responses and the relationships between response variables and predictors were analyzed using descriptive statistics and ordinal logistic regression models. With a response rate of 22.4% (n = 113), we found that nearly half of respondents (45.5%) do not always report non-native taxa, and of those who report, many (44.7%) do not always differentiate them from native taxa. Close to half of respondents (46.4%) also view the terminology of biological invasions as an obstacle to the reporting of non-native taxa. The ways in which checklist information is provided are varied, but mainly correspond to descriptive text and embedded tables with non-native species (when given) mentioned alongside native species. Only 13.4% of respondents mention to always provide the data in automation-friendly formats or its publication in biodiversity data repositories. Data on the distribution of non-native species are essential for monitoring global biodiversity change and preventing biological invasions. Despite its importance our results show an urgent need to improve the frequency, accessibility, and consistency of publication of these data.